Reliability of the Swedish version of the multidimensional outcome expectations for exercise scale (MOEES-SW) in a cardiac population. - Urell, Charlotte; Hellström, Karin; Johansson, Henrik; Breidenskog, Marie; Hagström, Emil; Bring, Annika (Physiotherapy Theory & Practice, 2022)
Translate and adapt the Multidimensional Outcome Expectations for Exercise Scale (MOEES) into Swedish language and to explore psychometric properties, in terms of test-retest reliability, internal consistency as well as factor structure and floor and ceiling effects, of the Swedish version of MOEES in cardiac patients. This prospective psychometrical study set in a Swedish cardiac rehabilitation outpatient clinic included 74 patients; age 318 years after acute coronary syndrome or that had undergone cardiac surgery. Translation and adaptation procedure of the MOEES followed established international guidelines. To evaluate test-retest reliability, relative (intra-class correlation coefficient ICC, 2.1)and absolute reliability (standard error of measurement (SEM) standard error of measurement % (SEM%), percentage of absolute agreement and Kappa coefficient for each item were calculated. Internal consistency was assessed with Cronbach´s alpha. The original 3-factor structure was tested with a confirmatory factor analysis. Floor and ceiling effects were calculated. In total, 60 patients, mean age 65 years, were included in the study. The test-retest showed for the three outcome expectations subscales (Physical, Self-evaluative and Social) ICC-values of 0.40 (CI 95% 0.20-0.58), 0.57 (0.39-0.71) and 0.72 (0.57–0.83), respectively. In general, the Kappa coefficients were low and varied between 0.11 and 0.44. Two questions had low loadings in the confirmatory factor analysis (<0.5) , contributing to a weak fit of the model. There was no floor effect, but the subscales physical and self-evaluative outcome expectation showed ceiling effects. This is the first study to analyse test-retest reliability of the translated version of MOEES into Swedish in cardiac patients and shows need for further development of the instrument before use in clinical practice and research.